Work life balance, job stress and job satisfaction among Touch ‘n Go employees / Nur Lyana Nor Azmi and Siti Nurain Mahadi - Nor Azmi, Nur Lyana; Mahadi, Siti Nurain (Faculty of Business and Management, 2015)
The main purpose behind conducting the study is to examine the relationship between work life balance, job stress and job satisfaction among Touch „n Go employees. The study has been undertaken among employees from different departments consists of Human Resource, Operational Support and Information Support with a total population of 130 employees. A sample size consists of 100 employees that have been chosen from 3 different departments at Touch „n Go to distribute questionnaire. Convenience sampling method has been used as sampling technique for the study. Questionnaire is the tool used by researcher in order collecting data for this research. Data has been analyzed through Statistical Package for Social Sciences (SPSS). Frequency analysis, Descriptive statistics, Correlation and Multiple Regression analysis has been applied to draw the results of the study. This is mainly to answer the research objectives. The findings of the study shown that there is a positive relationship between work life balance and job satisfaction which prove H1 hypothesis is accepted. The result for job stress indicates there is insignificant relationship between job stress and job satisfaction which H2 hypothesis is rejected. Results of the study is helpful for employees at Touch „n Go so that they can get better understanding about the relationship exist between work life balance, job stress and job satisfaction as a result employees can improve and contribute more toward company.